2019
DOI: 10.1002/acn3.50953
|View full text |Cite
|
Sign up to set email alerts
|

Length‐dependent MRI of hereditary neuropathy with liability to pressure palsies

Abstract: ObjectiveHereditary neuropathy with liability to pressure palsies (HNPP) is caused by heterozygous deletion of the peripheral myelin protein 22 (PMP22) gene. Patients with HNPP present multifocal, reversible sensory/motor deficits due to increased susceptibility to mechanical pressure. Additionally, age‐dependent axonal degeneration is reported. We hypothesize that length‐dependent axonal loss can be revealed by MRI, irrespective of the multifocal phenotype in HNPP.MethodsNerve and muscle MRI data were acquire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 34 publications
2
24
1
Order By: Relevance
“…Although volumetric muscle FF has been used as a monitoring biomarker in CMT1A, 11,15 its responsiveness may not be sufficient to show progression when FF is measured in early stage of diseases or over a short period 12,26 . Furthermore, the FF from a severely denervated muscle could be compromised by a “floor” effect, and would not be suitable for tracking the progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although volumetric muscle FF has been used as a monitoring biomarker in CMT1A, 11,15 its responsiveness may not be sufficient to show progression when FF is measured in early stage of diseases or over a short period 12,26 . Furthermore, the FF from a severely denervated muscle could be compromised by a “floor” effect, and would not be suitable for tracking the progression.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, muscle denervation causes muscle fiber degeneration that is replaced by intramuscular fat cells over time 10 . Therefore, the severity of intramuscular fat accumulation provides an indirect measure of axonal loss in motor nerves in patients with peripheral neuropathies, including CMT1A, 11 hereditary neuropathy with liability to pressure palsies (HNPP), 12 hereditary sensory neuropathy (HSN) 13 , and chronic inflammatory demyelinating polyneuropathy 14 …”
Section: Introductionmentioning
confidence: 99%
“…While results from MTC studies conducted in the central nervous system (CNS) are promising [27][28][29][30][31][32][33][34][35][36][37], data on the potential of MTC imaging in the peripheral nervous system are limited. To date, there have been two studies that applied MTC imaging in patients with peripheral neuropathies, but their results were controversial: while one study found that MTR does not differentiate between patients with hereditary neuropathy with liability to pressure palsies (HNPP) and controls, the other study demonstrated a strong correlation between decreasing sciatic nerve MTR values and higher grades of disability in patients with Charcot-Marie-Tooth disease [38,39]. The latter finding is supported by a recent study from our group, in which we found evidence that sciatic nerve MTR is decreased in patients with hereditary transthyretin amyloidosis with polyneuropathy and correlates well with electrophysiologic results and the Neuropathy Impairment Score of the Lower Limb [40].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has demonstrated a mild axonal loss in patients with HNPP using qMRI. 21 The axonal loss was quantified by the muscle FF. After axon degenerates, fat increases in denervated muscle.…”
Section: Fatigue In Patients With Hnpp Was Not Correlated With Axonalmentioning
confidence: 99%
“…After axon degenerates, fat increases in denervated muscle. 21 We therefore tested whether the axonal loss is related to the fatigue.…”
Section: Fatigue In Patients With Hnpp Was Not Correlated With Axonalmentioning
confidence: 99%